2014
DOI: 10.1016/j.jmr.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

New spectral–spatial imaging algorithm for full EPR spectra of multiline nitroxides and pH sensitive trityl radicals

Abstract: An algorithm is derived and demonstrated that reconstructs an EPR spectral-spatial image from projections with arbitrarily selected gradients. This approach permits imaging wide spectra without the use of the very large sweep widths and gradients that would be required for spectral-spatial imaging with filtered backprojection reconstruction. Each projection is defined as the sum of contributions at the set of locations in the object. At each location gradients shift the spectra in the magnetic field domain, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The proposed future directions include advances in the synthesis of multifunctional paramagnetic probes and progress in EPR-based imaging techniques such as RS EPR imaging 87 and Overhauser-enhanced MRI. 59,91 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed future directions include advances in the synthesis of multifunctional paramagnetic probes and progress in EPR-based imaging techniques such as RS EPR imaging 87 and Overhauser-enhanced MRI. 59,91 …”
Section: Discussionmentioning
confidence: 99%
“…A new approach to image reconstruction is being evaluated that is based on the concept of solving the inverse problem in a form of large system of linear equations using Tikhonov regularization. 87 It was demonstrated that the size of the problem can be reduce by one in the Fourier domain, which makes it possible to handle with a modern desktop computer. The new method has been shown to work in a less computationally demanding two-dimensional case.…”
Section: Multifunctional Imaging Of Paramagnetic Probesmentioning
confidence: 99%
“…Note: Specific instructions related to analysis of phantoms containing BMPO-OH 24 , pH sensitive TAM radicals 19,27 and redox sensitive dinitroxides 28 are provided in the literature.…”
Section: Execution Of Rapid Scan Experimentsmentioning
confidence: 99%
“…Magnetic field gradients are used to encode spatial information into EPR spectra, which are called projections. The spectral-spatial image is reconstructed from these projections 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Krishna laboratory (Subramanian et al, 2007). Published rapid-scan imaging experiments have been performed with phantoms of TCNQ (Subramanian et al, 2007), LiPc (Czechowski et al, 2014), nitroxides (Aminov, Tseitlin, & Salikhov, 1999; Biller et al, 2015; Biller et al, 2014b; M. Tseitlin et al, 2014) and pH-sensitive amino substituted trityl radicals (Elajaili, Biller, Tseitlin, et al, 2015).…”
Section: Examplesmentioning
confidence: 99%